Chinese Materials in the Jesuit Archives in Rome, 14th-20th Centuries : a Descriptive Catalogue : A Descriptive Catalogue. - Chan, Albert (Taylor and Francis, 2002)
The Jesuit Archives in Rome (Archium Romanum Societatus Iesu) contains books and manuscripts from the Ming (1369-1644) and Ching (1644-1911) dynasties on Chinese history, Chinese and Western philosophy, astronomy and other sciences; volumes by Westerners introducing Christian thought to the Chinese; and works by Chinese Christians comparing what they were taught by the Jesuits with the Buddhist, Taoist, and Confucian traditions. Many works deal with the famous Chinese rites controversy. There are also volumes that treat other religious groups such as the Muslims and the Jews. The archive has a.